Awareness of Public Elementary School Parents on the Legal Provisions of Anti-Child Labor Law: Basis for Intervention Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
The Philippine Anti-Child Labor Law (Republic Act 7658) is a statutory law aimed at protecting children under 15 years old from working in public or private establishments. It consists of two areas: Information Dissemination and Penalties. The law aims to promote awareness and prevent violations, with penalties such as fines or imprisonment. A study was conducted to determine the level of awareness of public elementary school parents in a second-class municipality during the 2021-2022 school year. The results showed that the majority of respondents were older, female, and from larger families. The overall awareness of parents on the law was "High," with a high level of awareness grouped by age, sex, family size, and average family income. However, there was no significant difference in awareness among respondents based on age, sex, family size, or average family income. The findings suggest that barangay authorities and school administration do not collaborate to address child labor issues, as the community lives in poverty and relies on cheap manual labor. Additionally, older respondents should be made aware of the penalties for violating provisions of Article 12 of the law.